Juliet, naked [videorecording (DVD)] - Byrne, Rose; Hawke, Ethan, 1970-; O'Dowd, Chris, 1980-; Hornby, Nick (Lionsgate, 2018)
The story of Annie, the long-suffering girlfriend of Duncan, and her unlikely transatlantic romance with once revered, now faded, singer-songwriter, Tucker Crowe, who also happens to be the subject of Duncan's musical obsession.